The New Methodologies for Learning how to Teach a Foreign Language by Using Virtual Tools - Rosales Ramírez, Víctor Fernando (2024)
This final report focuses in an online specialization course, developed from August, 2021, to February, 2022. This was the first experience that the Department of Foreign Languages had offering this innovating course. It served as a new modality that students could take as a substitute for the classic graduation work. In the new plan, students learned about how to apply technological strategies and how to exploit other tools that nowadays the technology offers us to be updated. One important thing is that the course was developed online by professors who were very capable to contribute to students´ learning and at the same time to prepare them to deal the technological and professional environment which have become so popular after the coronavirus pandemic. The experiences, main activities and principal course achievements are detailed in the present report. Key Words: Virtual Classroom ; Language Learning Theories ; Language Learning Strategy (LLS) ; Information and Communication Technologies (ICTs) and Asynchronous and Synchronous Communicative.